User Modeling, Adaptation, and Personalization 18th International Conference, UMAP 2010, Big Island, HI, USA, June 20-24, 2010. Proceedings - Bra, Paul.; Kobsa, Alfred; Chin, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the Second International Conference on User Modeling, Adaptation, and Personalization, held on Big Island, HI, USA, in June 2010. This annual conference was merged from the biennial conference series User Modeling, UM, and the conference on Adaptive Hypermedia and Adaptive Web-Based Systems, AH. The 26 long papers and 6 short papers presented together with 7 doctoral consortium papers, 2 invited talks, and 4 industry panel papers were carefully reviewed and selected from 161 submissions. The tutorials and workshops were organized in topical sections on intelligent techniques for web personalization and recommender systems; pervasive user modeling and personalization; user models for motivational systems; adaptive collaboration support; architectures and building blocks of web-based user adaptive systems; adaptation and personalization in e-b/learning using pedagogic conversational agents; and user modeling and adaptation for daily routines.
Keynote Speakers -- Modeling Emotion and Its Expression in Virtual Humans -- AdHeat $1 (BAn Influence-Based Diffusion Model for Propagating Hints to Personalize Social Ads -- Full Research Papers -- Can Concept-Based User Modeling Improve Adaptive Visualization? -- Interweaving Public User Profiles on the Web -- Modeling Long-Term Search Engine Usage -- Analysis of Strategies for Building Group Profiles -- Contextual Slip and Prediction of Student Performance after Use of an Intelligent Tutor -- Working Memory Span and E-Learning: The Effect of Personalization Techniques on Learners$1 (BPerformance -- Scaffolding Self-directed Learning with Personalized Learning Goal Recommendations -- Instructional Video Content Employing User Behavior Analysis: Time Dependent Annotation with Levels of Detail -- A User-and Item-Aware Weighting Scheme for Combining Predictive User Models -- PersonisJ: Mobile, Client-Side User Modelling -- Twitter, Sensors and UI: Robust Context Modeling for Interruption Management -- Ranking Feature Sets for Emotion Models Used in Classroom Based Intelligent Tutoring Systems -- Inducing Effective Pedagogical Strategies Using Learning Context Features -- (3z(BYes!(3y(B: Using Tutor and Sensor Data to Predict Moments of Delight during Instructional Activities -- A Personalized Graph-Based Document Ranking Model Using a Semantic User Profile -- Interaction and Personalization of Criteria in Recommender Systems -- Collaborative Inference of Sentiments from Texts -- User Modelling for Exclusion and Anomaly Detection: A Behavioural Intrusion Detection System -- IntrospectiveViews: An Interface for Scrutinizing Semantic User Models -- Analyzing Community Knowledge Sharing Behavior -- A Data-Driven Technique for Misconception Elicitation -- Modeling Individualization in a Bayesian Networks Implementation of Knowledge Tracing -- Detecting Gaming the System in Constraint-Based Tutors -- Bayesian Credibility Modeling for Personalized Recommendation in Participatory Media -- A Study on User Perception of Personality-Based Recommender Systems -- Compass to Locate the User Model I Need: Building the Bridge between Researchers and Practitioners in User Modeling -- Industry Papers -- myCOMAND Automotive User Interface: Personalized Interaction with Multimedia Content Based on Fuzzy Preference Modeling -- User Modeling for Telecommunication Applications: Experiences and Practical Implications -- Mobile Web Profiling: A Study of Off-Portal Surfing Habits of Mobile Users -- Personalized Implicit Learning in a Music Recommender System -- Short Research Papers -- Personalised Pathway Prediction -- Towards a Customization of Rating Scales in Adaptive Systems -- Eye-Tracking Study of User Behavior in Recommender Interfaces -- Recommending Food: Reasoning on Recipes and Ingredients -- Disambiguating Search by Leveraging a Social Context Based on the Stream of User$1 (Bs Activity -- Features of an Independent Open Learner Model Influencing Uptake by University Students -- Doctoral Consortium Papers -- Recognizing and Predicting the Impact on Human Emotion (Affect) Using Computing Systems -- Utilising User Texts to Improve Recommendations -- Semantically-Enhanced Ubiquitous User Modeling -- User Modeling Based on Emergent Domain Semantics -- (3z(BBiographic spaces(3y(B: A Personalized Smoking Cessation Intervention in Second Life -- Task-Based User Modelling for Knowledge Work Support -- Enhancing User Interaction in Virtual Environments through Adaptive Personalized 3D Interaction Techniques.s
Keywords: Computer science; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Optical pattern recognition; Computer Science; Data Mining and Knowledge Discovery; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Pattern Recognition